Newly isolated sporopollenin microcages from Platanus orientalis pollens as a vehicle for controlled drug delivery - Mujtaba, Muhammad; Sargın, İdris; Akyüz, Lalehan; Ceter, Talip; Kaya, Murat (Elsevier BV, 2017)
Sporopollenin microcages were produced from the pollens of Platanus orientalis. Paracetamol was loaded into the microcages. Pollen, sporopollenin, paracetamol and paracetamol-loaded sporopollenin microcages were characterized with FT-IR, TGA and SEM. The analytical analyses demonstrated that sporopollenin microcages were structurally intact, highly reticulated and thermally stable. The loading efficiency of the sporopollenin microcages was found to be 8.2% using the passive loading technique and 23.7% via evaporating loading technique. In vitro release and kinetics studies were performed to test the suitability of sporopollenin microcages for loading. These studies revealed that sporopollenin from P. orientalis can be suggested as a suitable carrier for drug loading and controlled release studies.
Keywords: Release kinetics; Release Kinetics; Carotenoids; Microcapsule; Biopolymers; Drug delivery; Spectroscopy, Fourier Transform Infrared; Pollen; Drug Delivery; Acetaminophen; 3. Good health